ANALYSIS OF THE EFFECT OF SO2 GAS ON RESPIRATORY DISEASE LEVEL IN SURABAYA CITY - Santoso, Adi Nugroho; Razif, Mohamad - (ENVIROSAN : Jurnal Teknik Lingkungan, 2022)
Â  Indonesia is one of the developing and populated countries. Along with increasing development, especially industrial and transportation development, it can have a negative impact, namely the low quality of the surrounding air and the high number of cases of respiratory diseases. The national health profile data shows that 46% of community diseases originate from: Respiratory symptoms (43%), Pneumonia (1.7%), and Asthma (1.3%). SO2 gas is an air pollutant and is a risk factor for respiratory disease. This study aims to analyze the effect of SO2 gas levels in the air on the number of cases of respiratory disease in the city of Surabaya. The research method used is correlation analysis. The data used is secondary data obtained from IKPLHD Surabaya for the last 5 years and direct measurements from air quality measurement stations. The results showed that the air quality in the city of Surabaya for the last 5 years was still relatively good, with SO2 levels of 8.9 g/m3. The number of cases of respiratory disease was 439,013 cases. There is a relationship between cases of respiratory disease with SO2 levels with a correlation coefficient of 0.668 (Ï = 0.0007).